Pengendalian Persediaan Bahan Baku Terhadap Kelancaran Proses Produksi Pada UD Tiga Berlian Dengan Metode Material Requirement Planning - Firmansyah, Muhammad Irfan; Sumarsono, Sumarsono (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD Tiga Berlian is a company engaged in the food industry.Based on sales data, the Decomposition method is the best forecasting method because it has the lowest MAPE, MAD and MSD values. Therefore, researchers can conclude that sales for the last 12 months, namely January to December 2025, were 12723, 10006, 11703, 10708, 13219, 12723, 10006, 11703,10708, 13219, 12723,10006 kg. The final process to obtain raw material requirement data is to create an MRP report using the EOQ technique. In 2025, namely in brown sugar material, a total of 48,583 kg is needed, sago flour requires 53,823 kg, wheat flour requires 27,049 kg, salt 693 kg, shrimp 2,786 kg, fish 6,819 kg. This report is a comprehensive report on the optimal raw material requirements for petis products. With this MRP method, the company can provide raw materials